CHARACTERISTICS OF DEVIANT BEHAVIOR OF ADOLESCENTS AND THE REASONS FOR ITS APPEARANCE (Pedagogy of Higher and Secondary Education, 2022)
The artikale includes the analysis of special literature concerning characteristics of deviation behaviour teenager andcause its beginning.